Profession and Professional Work in Adult Education in Europe - Ekkehard Nuissl (Firenze University Press, 2010)
In the recent decade it became more important to reflect about the work which is done in adult education, who is doing it and how he is qualified to do that. It is somehow the reaction on the shift to the learner, who is more and more seen as a self-directed and self-responsible actor apparently without the need of any professional help. So the author would like to take a look on trends and challenges in the professional development of adult educators.